MINI-CHOLECYSTECTOMY: A FEASIBLE OPTION - Saeed, Nadia; Nasir, Tauqeer; Burki, Bilal; Channa, Ghulam Asghar (Journal of Ayub Medical College Abbottabad, 2010)
Background: In standard or conventional cholecystectomy gallbladder is approach through a subcostal incision of 7-10 Cm. New technique and procedures have evolved, aiming at decreased tissue damage, pain, hospital stay and complications. This study was conducted to assess cholecystectomy through 5 Cm mini-laparotomy. Methods: This study was conducted at Department of General Surgery, Ward-26, Jinnah Postgraduate Medical Centre, Karachi from January, 2008 to January, 2009. Both sexes irrespective of age were included in this study. Ninety cases were females and 10 were male. Mean age of the patients was 48 years. Minicholecystectomy was performed on patients and results evaluated as percent and frequency. Results: This study included 100 patients with cholelithiasis. Mini-cholecystectomy was possible in 95% cases, and in 5 cases incision had to be extended to conventional cholecystectomy. The average operating time was 50 minutes and postoperative hospital stay was 2-days and postoperative complications like minor biliary leak, haemorrhage and wound infection was seen in 10 cases. Conclusion: Mini-cholecystectomy is a safe procedure with shorter operative time, fewer complications, better prognosis, and less of postoperative hospital stay. It may be recommended as a procedure of choice where laparoscopic facilities are not available. Keywords: Gallbladder, Cholelithiasis, Mini-cholecystectomy, Mini-laparotomy